Burst fracture Th 9-10 treat with Transthoracal Corpectomy and stabilization: A Cases Report - Manurung, Halim Rahman; Ibrahim, Sabri; Dharmajaya, Ridha (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2019)
Abstract. Spinal fracture and dislocation are among the most feared injuries by patients and physicians alike, as the consequences can be devastating, ranging from mild pain and discomfort to severe paralysis and even death. Spinal trauma is commonly found in patients admitted to level-one trauma centers after serious accidents like traffic, falling, and sports accidents.Injuries of the cervical spine account for one third of spinal fractures and half to two thirds of all spinal cord injuries.In the thoracolumbar spine, the most common unstable fracture is the burst fracture. Altogether, burst fractures have been reported to account for about 15% of spinal injuries.Incidence of burst fractures peaked at the thoracolumbar junction and between levels T5 and T8. In 10% of cases,more than one burst fracture was seen, thereof 53% on noncontiguous levels. Main accident mechanisms were falls, traffic, and sports. Neurological deficit was highest in patients with burst fractures of the cervical spine, independent of accident mechanism, and lowest in thoracolumbar junction fractures. Burst fractures occur frequently in high energy traumas and are most commonly associated with falling and traffic accidents.Multiple burst fractures occur in 10% of cases, half thereof on noncontiguous levels.Access to the anterior thoracic spine via the transthoracic approach (via thoracotomy) can be used for decompression and fusion. To perform adequate decompression and stabilization of the thoracic spine, obtaining good exposure is a must. Preservation and protection of the vascular structures in the thoracic cavity is the key to such an exposure. Preoperative workup should include imaging modalities (plain rontgens, MRI/CT scan) to specifically define the area of decompression. If a tumor is being evaluated, CT angiography and embolization are helpful in preoperative planning. Assistance by a thoracic surgeon for exposure is highly recommended.